2014
DOI: 10.1080/17565529.2014.886993
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerability to multiple stressors in coastal communities: a study of the Andaman coast of Thailand

Abstract: Abstract:Vulnerability and adaptation to climate change has become a dominant theme in development and conservation research and work. Yet coastal communities are facing a wider array of different stressors that affect the sustainability of natural resources and the adaptive capacity of local residents. The ability of communities and households to adapt is influenced by the nature, number, and magnitude of the changes with which they have to contend. In this paper, we present the range of 36 socio-economic (i.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(43 citation statements)
references
References 37 publications
0
43
0
Order By: Relevance
“…This cooperation was evident in the way that they shared transport costs, took turns to do shopping and generally helped each othermaking this one of the most important coping strategies displayed by this community. 5,9,12 Participants observed that the transformation of the area from productive farms to holiday houses and non-crop farms had resulted in the systematic reduction of employment opportunities. As agricultural activities and associated employment decreased, fishing became an increasingly important livelihood strategy.…”
Section: Vermaaklikheid: the Reacting Fishersmentioning
confidence: 99%
See 1 more Smart Citation
“…This cooperation was evident in the way that they shared transport costs, took turns to do shopping and generally helped each othermaking this one of the most important coping strategies displayed by this community. 5,9,12 Participants observed that the transformation of the area from productive farms to holiday houses and non-crop farms had resulted in the systematic reduction of employment opportunities. As agricultural activities and associated employment decreased, fishing became an increasingly important livelihood strategy.…”
Section: Vermaaklikheid: the Reacting Fishersmentioning
confidence: 99%
“…[1][2][3][4] Coastal communities that rely on fisheries are subjected to an array of political, regulatory, socio-economic and biophysical stressors 5 , and remain exposed to multiple stressors [6][7][8][9] at various temporal and geographical scales. Response strategies to these changes, broadly classified as either reacting, coping or adapting (see supplementary material for a definition of concepts used in this paper), are also influenced by actions at multiple scales.…”
Section: Introductionmentioning
confidence: 99%
“…Due to increased frequency and severity of climate change and environmental disasters in recent years, traditional environmental impact studies have gradually transformed into vulnerability and resilience (i.e., adaptability) studies [1]. That is, recent studies have focused on methods of assessing the capacity of a society to continue operations after it has been impacted by disasters, and its capacity to recover after the impact [5,12,[15][16][17].…”
Section: Environmental Change and Vulnerabilitymentioning
confidence: 99%
“…This information can then be used to develop strategies that inform adaptation governance. Although domestic and international studies apply different definitions of vulnerability, the two main streams are "biophysical vulnerability" to natural disasters and "social vulnerability" due to socio-economic factors [12,16,20,21].…”
Section: Environmental Change and Vulnerabilitymentioning
confidence: 99%
“…The impacts of contemporary social and environmental change are particularly glaring for coastal communities, exposed to and engaged in the dynamics of both marine and terrestrial systems (Bunce et al, 2010;Ommer, 2007;Bennett et al, 2015). Coastal zones face some of the greatest biophysical impacts of climate change, including myriad consequences of rising sea levels (e.g., coastal erosion and sea water inundation) and increased variability of storms, drought, and other extreme weather events (Bunce et al, 2010).…”
Section: Introductionmentioning
confidence: 99%